# Simultaneous Linear Equations/Examples/Arbitrary System 6

## Example of Simultaneous Linear Equations

Let $S$ denote the system of simultaneous linear equations:

 $\ds x + y + 2 z$ $=$ $\ds -1$ $\ds -x + z$ $=$ $\ds -1$ $\ds -x + y + 4 z$ $=$ $\ds -3$

$S$ has as its solution set:

 $\ds x$ $=$ $\ds z + 1$ $\ds y$ $=$ $\ds z - 2$

where $z$ can be any number.

## Proof

We express $S$ in matrix representation:

$\begin {pmatrix} 1 & 1 & 2 \\ -1 & 0 & 1 \\ -1 & 1 & 4 \end {pmatrix} \begin {pmatrix} x \\ y \\ z \end {pmatrix} = \begin {pmatrix} -1 \\ -1 \\ -3 \end {pmatrix}$

and consider the augmented matrix:

$\begin {pmatrix} \mathbf A & \mathbf b \end {pmatrix} = \paren {\begin {array} {ccc|c} 1 & 1 & 2 & -1 \\ -1 & 0 & 1 & -1 \\ -1 & 1 & 4 & -3 \end {array} }$

In the following, $\sequence {e_n}_{n \mathop \ge 1}$ denotes the sequence of elementary row operations that are to be applied to $\begin {pmatrix} \mathbf A & \mathbf b \end {pmatrix}$.

The matrix that results from having applied $e_1$ to $e_k$ in order is denoted $\begin {pmatrix} \mathbf A_k & \mathbf b_k \end {pmatrix}$.

$e_1 := r_2 \to r_2 + r_1$

$e_2 := r_3 \to r_3 + r_1$

Hence:

$\begin {pmatrix} \mathbf A_2 & \mathbf b_2 \end {pmatrix} = \paren {\begin {array} {ccc|ccc} 1 & 1 & 2 & -1 \\ 0 & 1 & 3 & -2 \\ 0 & 2 & 6 & -4 \\ \end {array} }$

$e_3 := r_3 \to r_3 - 2 r_2$

Hence:

$\begin {pmatrix} \mathbf A_3 & \mathbf b_3 \end {pmatrix} = \paren {\begin {array} {ccc|ccc} 1 & 1 & 2 & -1 \\ 0 & 1 & 3 & -2 \\ 0 & 0 & 0 & 0 \\ \end {array} }$

$e_4 := r_1 \to r_1 - r_2$

Hence:

$\begin {pmatrix} \mathbf A_4 & \mathbf b_4 \end {pmatrix} = \paren {\begin {array} {ccc|ccc} 1 & 0 & -1 & 1 \\ 0 & 1 & 3 & -2 \\ 0 & 0 & 0 & 0 \\ \end {array} }$

Thus $z$ is not restricted, and can be anything, leaving us with:

 $\ds x$ $=$ $\ds z + 1$ $\ds y$ $=$ $\ds z - 2$

as the solution set:

$\blacksquare$